Historical perspectives on democratic police reform: Institutional memory, narratives and ritual in the post-war Italian police, 1948–1963 - Dunnage, Jonathan (Policing and society, 2017)
The article analyses the occupational culture of the Italian Interior Ministry police after the Second World War, following the demise of Benito Mussolini's fascist dictatorship. In undertaking this, the article largely focuses on how the history, values and objectives of the post-war Italian police were narrated in professional literature and institutional correspondence and represented in celebrative and commemorative rituals, and the ways in which the recent experience of the dictatorship determined this. While the article presents a historical case, it also intends to stimulate more general reflection on the ways in which aspects of police occupational culture formed during dictatorships survive and/or evolve during and following periods of regime change and on how this can be studied. A research approach which focuses, for example, on the aesthetics and language of police ceremonies and/or the manner in which the institutional history of a police force is internally narrated could be enlightening for today's scholars and donors of police reform. The Italian case shows how police forces emerging from dictatorships may formally stress their democratic credentials, but can ‘normalise’ controversial behaviour under a previous dictatorship by conceptually separating professional functions from the broader ideological implications of such functions, whilst still being driven by cultural practices and strategies which they had learned under that regime.